PThe Role of Family Welfare Movement Team (TP-PKK) in Creating Child Protection in Fulfillment of Education Rights During the Covid-19 Pandemic - Sri Ayu Septinawati; Yenny Aman Serah; Anita Yuliastini; Rini Setiawati (UNUSA Press, 2021)
Covid-19 has a significant impact on the life of the Indonesian, including fulfilling the right to education for children. With the social distancing, the Ministry of Education in Indonesia issued a policy by closing schools and replacing the teaching and learning process using an online system. However, there are obstacles during online learning. One of them is parents' unpreparedness to accompany their children. It is necessary to build motivation for parents or families, especially mothers. Children as the goal of education and the realization of child protection have been regulated in legislation. The authors conducted the community service activity with an online legal counseling method to Family Welfare Movement Team (here and after called TP-PKK) in Regency/City throughout West Kalimantan. In conclusion, TP-PKK has a role in creating child protection in fulfillment of education rights during the Covid-19 pandemic. Legal counseling could be carried out widely and sustainably to motivate parents or families to assist their children in the online learning process, so child protection is realized